KEPENTINGAN INDONESIA MERATIFIKASI INTERNATIONAL COFFEE AGREEMENT - Handayana Putra Kurniawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Indonesia is the third coffee producer in the world. These coffee exports are the second largest of Indonesia’s national income from plantation sector after crude palm oil. These national incomes have to be maintained. Yet, Indonesia produces low grade quality coffee and difficult to compete on international market. Indonesia has to take a foreign policy to solve that problem. Then, Indonesia ratified International Coffee Agreement 2007. Indonesia has national interest on that policy. This research describes Indonesia’s national interest ratifying International Coffee Agreement 2007. This research uses Snyder’s foreign policy theory and Donald E Nuchterlain’s national interest theory. The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles, internet and other media. This research focuses on finding Indonesia’s national interest on ratifying International Coffee Agreement 2007. Coffee exports are very important for Indonesia. Though Indonesian coffee has low grade quality, it gives big national income for Indonesia. Indonesia’s national interests on ratifying International Coffee Agreement 2007 to be Perpres No. 63 tahun 2008 are to increase Indonesia’s coffee quality and to maintain national incomes. Indonesia gets transfer of technology and being helped to find new market to export coffee by International Coffee Organization. Keywords: International Coffee Agreement, national interest, foreign policy.